Hereditary transthyretin amyloidosis incidentally diagnosed by video-associated lung surgery for lung cancer: A case report - Katsuhiro Itogawa; Shintaro Sato; Hideaki Yamakawa; Keiichi Akasaka; Masako Amano; Akiko Adachi; Hidekazu Matsushima (Respiratory Medicine Case Reports)
Pulmonary involvement associated with transthyretin amyloidosis is a relatively uncommon presentation among many systemic symptoms. However, in recent times, several definitive treatments have been newly approved, thus the importance of diagnosing previously overlooked cases has been increasing. This report describes an incidentally diagnosed case with a pulmonary lesion. A 76-year-old male with a history of obstructive sleep apnea syndrome, bilateral carpal tunnel syndrome, and lumbar canal stenosis was presented with a 25mm right lower lobe nodule identified through a computed tomography conducted at an outpatient clinic. Lung cancer was suspected and the following thoracoscopic segmentectomy revealed a diagnosis of adenocarcinoma in situ. In addition, further pathological investigation of the background lung tissue revealed deposition of amyloid transthyretin (TTR), although no radiological findings suggestive of pulmonary amyloidosis were present. A genetic mutation screening test revealed pathological TTR gene mutation of heterozygous Tyr114His (p.Tyr134His). Thus, the diagnosis of hereditary transthyretin amyloidosis was made, and the subsequent investigation identified familial amyloid polyneuropathy. Finally, treatment with vutrisiran, a small interfering RNA (siRNA) targeting the TTR gene, was successfully initiated. Physicians need to be aware that unidentified amyloidosis may be diagnosed incidentally from a biopsied or resected specimen for another purpose. Diagnosing systemic amyloidosis that may otherwise be overlooked would enable patients to receive benefits from the definitive therapy.